2020
DOI: 10.1007/s13178-020-00506-1
|View full text |Cite
|
Sign up to set email alerts
|

“INSIDE” Project on Sexual Health in Spain: Sexual Life During the Lockdown Caused by COVID-19

Abstract: Introduction The COVID-19 pandemic is becoming a major hazard to public health worldwide. This is causing a significant impact on life and physical health, as well as on the psychological well-being of the general population. Since the emotional distress and the social restrictions caused by this epidemic, it must be expected that its impact will also extend to sexual health. The purpose of this study, the first including a large sample of the Spanish general population, was to analyze sexual beha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
80
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 49 publications
13
80
0
7
Order By: Relevance
“…In a Spanish study ( Ballester-Arnal et al, 2020 ), the total sample was divided into three quite similar subgroups. Approximately one third, 35.9%, stated that they had greater sexual desire during confinement, 34.9% had less desire and 29.1% nearly the same.…”
Section: Sexual Desirementioning
confidence: 99%
“…In a Spanish study ( Ballester-Arnal et al, 2020 ), the total sample was divided into three quite similar subgroups. Approximately one third, 35.9%, stated that they had greater sexual desire during confinement, 34.9% had less desire and 29.1% nearly the same.…”
Section: Sexual Desirementioning
confidence: 99%
“…Seventeen studies assessed sexual activity and desire during the pandemic among the general public. [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111] Ten studies indicated that the pandemic had affected participants' sexual lives. 97-109 111 A Chinese cross-sectional observational quantitative study found that the number of sexual partners decreased during the pandemic.…”
Section: General Publicmentioning
confidence: 99%
“…Dans une étude espagnole ( Ballester-Arnal et al, 2020 ), 47,7 % des participants, ont déclaré que leur vie sexuelle a été affectée par la pandémie et surtout les femmes. 37,9 % ont déclaré une diminution de leur activité sexuelle et seulement 14,4 % d’entre eux, un désir plus faible.…”
Section: Désir Sexuelunclassified